Design, Synthesis, Mode of Action and Herbicidal Evaluation of Quinazolin-4(3H)-one Derivatives Based on Aryloxyphenoxypropionate Motif - Chaochao Wang; Ke Chen; Na Li; Shuyue Fu; Pan Li; Lusha Ji; Guoyun Liu; Xuekun Wang; Kang Lei (Agronomy, 2022)
To discover new acetyl-CoA carboxylase (ACCase) inhibiting-based herbicides, twenty-nine novel quinazolin-4(3H)-one derivatives were designed and synthesized based on the aryloxyphenoxypropionate motif. The bioassay results showed that most of the target compounds showed better pre-emergent herbicidal activity against monocotyledonous weeds in a greenhouse. Especially, when applied at 375 g ha−1 under pre-emergence conditions, compound QPP-7 displayed excellent herbicidal activity against monocotyledonous weeds (i.e., E. crusgalli, D. sanguinalis, P. alopecuroides, S. viridis, E. indica, A. fatua, E. dahuricu, S. alterniflora) with inhibition rate >90%, and displayed excellent crop safety to O. sativa, T. aestivum, G. spp, and A. hypogaea. The study of structure-activity relationship (SAR) revealed that the herbicidal activity of target compounds is strongly influenced by the spatial position of R group and the bulk of R1 group on quinazolin-4(3H)-one, and the (R = 6-F, R1 = Me) pattern is confirmed as the optimal orientation. Furthermore, the molecular docking study and the good inhibitory activity of QPP-7 against E. crusgalli ACCase enzyme (IC50 = 54.65 nM) indicated that it may be a ACCase inhibitor. Taken together, the present work demonstrated that compound QPP-7 could serve as a potential lead structure for further developing novel ACCase inhibiting-based herbicide.